Haiti: a human rights nightmare (Lawyers Committee for Human Rights New YorkUS, 1992)
Examines the human rights situation in the country since the coup, with particular focus on events in May, June and July 1992. Exposes as a sham the human rights rationale used to justify the removal of President Aristide.
DC